Doing challenging research studies in a patient-centred way: a qualitative study to inform a randomised controlled trial in the paediatric emergency care setting. Issue 5 (15th May 2014) - Woolfall, Kerry; Young, Bridget; Frith, Lucy; Appleton, Richard; Iyer, Anand; Messahel, Shrouk; Hickey, Helen; Gamble, Carrol
Abstract : Objective: To inform the design of a randomised controlled trial (called EcLiPSE) to improve the treatment of children with convulsive status epilepticus (CSE). EcLiPSE requires the use of a controversial deferred consent process. Design: Qualitative interview and focus group study. Setting: 8 UK support groups for parents of children who have chronic or acute health conditions and experience of paediatric emergency care. Participants: 17 parents, of whom 11 participated in telephone interviews (10 mothers, 1 father) and 6 in a focus group (5 mothers, 1 father). 6 parents (35%) were bereaved and 7 (41%) had children who had experienced seizures, including CSE. Results: Most parents had not heard of deferred consent, yet they supported its use to enable the progress of emergency care research providing a child's safety was not compromised by the research. Parents were reassured by tailored explanation, which focused their attention on aspects of EcLiPSE that addressed their priorities and concerns. These aspects included the safety of the interventions under investigation and how both EcLiPSE interventions are used in routine clinical practice. Parents made recommendations about the appropriate timing of a recruitment discussion, the need to individualise approaches to recruiting bereaved parents and the use of clear written information. Conclusions: Our study provided information to help ensure that a challenging trial was patient centred in its design. We will use our findings to help EcLiPSE practitioners to: discuss potentially threatening trial safety information with parents, use open-ended questions and prompts to identify their priorities and concerns and clarify related aspects of written trial information to assist understanding and decision-making.